RACIAL DISCRIMINATION THROUGH DIDO AS THE MAIN CHARACTER IN BELLE FILM - Ni Zha Zha Sufiana; M. Natsir; Chris Asanti (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The purpose of this thesis is to identify the discrimination that happened towards Dido as the main female character in Belle film. The film tells the story about a mulatto woman who receives racial discrimination in society because of her racial background. This thesis uses Gordon Allport’s theory of discrimination in which he explained the types of discrimination are antilocution, avoidance, discrimination, physical attack, and extermination. Qualitative research design was employed in conducting this research. The data are taken from dialogues, conversations, narrations, and screenshots that are related to racial discrimination towards Dido. From the five types of discrimination by Allport, there were only three types of discrimination that were happened towards Dido. They were antilocution, avoidance, and discrimination. Discrimination is the most prominent one in this thesis. Hence, it can be assumed when discrimination escalated, it can lead to an extreme action such as physical attack and extermination that happened towards the slave in the film.